Safety and Immunogenicity of a New Inactivated Polio Vaccine Made From Sabin Strains: A Randomized, Double-Blind, Active-Controlled, Phase 2/3 Seamless Study - Capeding M.R. (2023)
Background. A new inactivated polio vaccine made from Sabin strains (sIPV) was developed as part of the global polio eradication initiative. Methods. This randomized, double-blind, active-controlled, phase 2/3 seamless study was conducted in 2 stages. Healthy infants aged 6 weeks were randomly assigned to receive 3 doses of 1 of 4 study vaccines at 6, 10, and 14 weeks of age (336 received low-, middle-, or high-dose sIPV, or conventional IPV [cIPV] in stage I, and 1086 received lot A, B, or C of the selected sIPV dose, or cIPV in stage II). The primary outcome was the seroconversion rate 4 weeks after the third vaccination. Results. In stage I, low-dose sIPV was selected as the optimal dose. In stage II, consistency among the 3 manufacturing lots of sIPV was demonstrated. The seroconversion rates for Sabin and wild strains of the 3 serotypes after the 3-dose primary series were 95.8% to 99.2% in the lot-combined sIPV group and 94.8% to 100% in the cIPV group, proving the noninferiority of sIPV compared to cIPV. No notable safety risks associated with sIPV were observed. Conclusions. Low-dose sIPV administered as a 3-dose vaccination was safe and immunogenic compared to cIPV.